Incorporation of tritiated thymidine by epithelial and interstitial cells in bronchiolar-alveolar regions of asbestos-exposed rats. - Brody, A. R. (1989)
Inhaled asbestos causes progressive interstitial lung disease. The authors have performed a series of studies to elucidate early pathogenetic events at sites of fiber deposition in asbestos-exposed rats. This study reports that a single 5-hour exposure to chrysotile asbestos induces significant increases in incorporation of tritiated thymidine (3HTdR) into nuclei of epithelial and interstitial cells of bronchiolar-alveolar regions. No cell populations in air-exposed or carbonyl iron-exposed control animals exhibited more than 1% labeling at any point in time. Immediately after the 5-hour asbestos exposure, incorporation was normal. By 19 hours after exposure there was a significant increase in incorporation of 3HTdR, particularly by Type II epithelial cells of the first alveolar duct bifurcations. The greatest increase in degree of incorporation (up to 18-fold) was observed 24 hours after exposure, and increased percentages of 3HTdR-labeled cells were maintained through the 48 hours postexposure period. Normal labeling was present by 8 days after exposure, and this level remained through the 1-month period studied. This apparent mitogenic response correlates with increased numbers of bronchiolar-alveolar epithelial and interstitial cells demonstrated by ultrastructural morphometry in correlative studies. The authors speculate that the incorporation of 3HTdR could be induced by the direct effects of inhaled fibers or by mitogenic factors released from macrophages attracted to the inhaled asbestos.